505 change of direction asymmetry magnitude decreases according to chronological age in male and female elite youth tennis players: results from an 11-year longitudinal study - D'Hondt, J.; Chapelle, L.; D'Hondt, E.; Clarys, P. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Functional interlimb asymmetry is inherent and can be exacerbated by practicing sports. Predominantly unilateral sports, such as tennis, can potentially increase the magnitude of functional asymmetry. For example, tennis strokes are more often executed on one side of the court, as players tend to use their forehand more than their backhand, resulting in side-to-side differences in COD (i.e., change of direction) tasks. Given that asymmetry in COD already occurs at an early age, and that functional asymmetry has been reported to affect athletic performance, this study aimed to examine the development of 505 COD asymmetry longitudinally in youth elite tennis players.